2011
DOI: 10.1371/journal.pone.0025655
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Insulin Receptor Substrate (IRS)-1 Inhibits Myogenic Differentiation through Nuclear Exclusion of Foxo1 in L6 Myoblasts

Abstract: Insulin-like growth factors (IGFs) are well known to play essential roles in enhancement of myogenic differentiation. In this report we showed that initial IGF-I signal activation but long-term IGF-1 signal termination are required for myogenic differentiation. L6 myoblast stably transfected with myc-epitope tagged insulin receptor substrate-1, myc-IRS-1 (L6-mIRS1) was unable to differentiate into myotubes, indicating that IRS-1 constitutive expression inhibited myogenesis. To elucidate the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…Moreover, KLF1 was strongly upregulated in IBxDU pigs (25.61), which suggest an important role of this TRF. Other important TRFs identified in the performed analysis were FOS and FOXO1 , involved in muscle differentiation and metabolism [63], but also in the regulation of adipogenic genes (as PPARG ) expression and IMF accumulation [54, 62]. These TRFs were also previously identified in BF muscle of newborn piglets [30].…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, KLF1 was strongly upregulated in IBxDU pigs (25.61), which suggest an important role of this TRF. Other important TRFs identified in the performed analysis were FOS and FOXO1 , involved in muscle differentiation and metabolism [63], but also in the regulation of adipogenic genes (as PPARG ) expression and IMF accumulation [54, 62]. These TRFs were also previously identified in BF muscle of newborn piglets [30].…”
Section: Discussionmentioning
confidence: 86%
“…Retrovirus production and infection were performed as described previously (26). Infected cells were selected with G418 or puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…DNA synthesis was measured as described previously (26). For cell proliferation assays, 4.0 ϫ 10 4 cells were grown in a 35-mm dish in DMEM supplemented with 1% fetal bovine serum (FBS) with or without 100 ng/ml of IGF-I.…”
Section: Methodsmentioning
confidence: 99%
“…L6 cells were maintained at 37 • C in a humidified 5% CO 2controlled atmosphere in DMEM supplemented with 10% FBS, 0.1% NaHCO 3 , 50 IU/mL penicillin, and 50 µg/mL streptomycin. L6 cell differentiation was induced as previously described (12). Passage number of cells used in experiments was 8∼15.…”
Section: Cell Culturementioning
confidence: 99%
“…For example, IRS-1 knockdown C2C12 myoblasts had defects in myogenesis (11). On the other hand, we previously reported that IRS-1 overexpression inhibited myogenic differentiation in L6 myoblasts through continuous Foxo1 inhibition that might cause repression of MyHC at the late stage of differentiation (12).…”
Section: Introductionmentioning
confidence: 98%